The Effect Of Product Knowledge and Product Brand Image On The Decision To Use A Product Through Trust As A Mediation Variable (A Study Of IAIN Bone Students Using BSI Products) - Rezky Awalia Amanda M; Muhammad Rakib; Rahmatullah (LP2M IAIN Palopo, 2025)
This study aims to: (1) analyze the influence of product knowledge on the decision to use Bank Syariah Indonesia (BSI) products; (2) examine the influence of brand image on the decision to use the products; and (3) assess the role of trust as a mediating variable in the relationship between product knowledge and brand image and the decision to use the products. A quantitative approach was used in this study, using Partial Least Square–Structural Equation Modeling (PLS-SEM) analysis using the SmartPLS application. This study involved 100 IAIN Bone students selected through purposive sampling based on their experience using BSI services. The results showed that product knowledge had a positive but insignificant effect on the decision to use BSI products. Conversely, brand image had a positive and significant effect, indicating that perceptions of BSI's reputation and credibility were dominant factors in driving the decision to use. Furthermore, trust was shown to have a significant positive effect as a mediating variable that strengthened the relationship between product knowledge and brand image on the decision to use the products.